Penerapan Media Pembelajaran Game Edukasi Wordwall untuk Meningkatkan Keaktifan Siswa dalam Pembelajaran Matematika di Kelas 1 - Wati, Mirna; Meylia Hindarwati; Mardliana Zulfa Al Badry; Bagus Nurul Iman; Nurul Ariyanti; Rani Eka Lestari (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The learning interest of students at SDN Silih Asih 2 during learning varies greatly. However, based on the results of observations, most students are less active in participating in learning activities in class, especially in Mathematics. This problem occurs due to the lack of use of interesting and enjoyable learning media for students. This study aims to prove whether the application of Wordwall educational game media can improve student learning activity in Mathematics in Class 1. The research conducted was Classroom Action Research (CAR) involving 20 students. Data collection included direct observation, interviews and questionnaires. The results of the study showed that the application of Wordwall educational game-based learning media can improve student activity. This is evidenced by an increase in the average student activity of 55% from cycle I to cycle II. This increase shows that the application of Wordwall educational game learning media is effective in improving student activity in learning mathematics in class 1 at SDN Silih Asih 2.